Amniotic fluid cathepsin-G in pregnancies complicated by the preterm prelabor rupture of membranes. (2nd September 2017) - Musilova, Ivana; Andrys, Ctirad; Drahosova, Marcela; Soucek, Ondrej; Pliskova, Lenka; Stepan, Martin; Bestvina, Tomas; Maly, Jan; Jacobsson, Bo; Kacerovsky, Marian
Abstract: Objective : The aim of this study was to evaluate the amniotic fluid cathepsin-G concentrations in women with preterm prelabor rupture of membranes (PPROM) based on the presence of the microbial invasion of the amniotic cavity (MIAC) and/or intra-amniotic inflammation (IAI). Methods : A total of 154 women with singleton pregnancies complicated by PPROM were included in this study. Amniotic fluid samples were obtained by transabdominal amniocentesis. Amniotic fluid cathepsin-G concentrations were assessed by ELISA. MIAC was determined using a non-cultivation approach. IAI was defined as an amniotic fluid bedside interleukin-6 concentration ≥ 745 pg/mL. Results : Women with MIAC had higher amniotic fluid cathepsin-G concentrations than women without MIAC (with MIAC: median 82.7 ng/mL, versus without MIAC: median 64.7 ng/mL; p  = 0.0003). Women with IAI had higher amniotic fluid cathepsin-G concentrations than women without this complication (with IAI: median 103.0 ng/mL, versus without IAI: median 66.2 ng/mL; p  < 0.0001). Women with microbial-associated (with both MIAC and IAI) IAI and sterile (IAI without MIAC) IAI had higher amniotic fluid cathepsin-G concentrations than women with colonization (MIAC without IAI) and women without both MIAC and IAI ( p  < 0.0001). Conclusions : The presence of either microbial-associated or sterile IAI was associated with increased amniotic fluid cathepsin-G concentrations in pregnancies complicated by PPROM. Amniotic fluid cathepsin-G appears to be a potential marker of IAI.